2022
DOI: 10.1111/ijac.14132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a new nonoxide additive, Y3Si2C2, on the thermal conductivity and mechanical properties of Si3N4 ceramics

Abstract: Enhancement of the thermal conductivity of silicon nitride is usually achieved by sacrificing its mechanical properties (bending strength). In this study, β-Si 3 N 4 ceramics were prepared using self-synthesized Y 3 Si 2 C 2 and MgO as sintering additives. It was found that the thermal conductivity of the Si 3 N 4 ceramics was remarkably improved without sacrificing their mechanical properties. The microstructure and properties of the Si 3 N 4 ceramics were analyzed and compared with those of the Y 2 O 3 -MgO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This increase was due to the reduction of internal F I G U R E 7 Relation between thermal conductivity and bending strength for Si 3 N 4 sintered by different routes. GPS, 14,28,[40][41][42][43][44][45] gas pressure sintered; SRBSN, sintered reaction-bonded silicon nitride 2,16,18,46,47 ; HP, hot pressing [48][49][50] ; SPS, spark plasma sintering 51,52 ; PLS, pressureless sintering 33 ; HPFS, hot-pressing flowing sintering.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…This increase was due to the reduction of internal F I G U R E 7 Relation between thermal conductivity and bending strength for Si 3 N 4 sintered by different routes. GPS, 14,28,[40][41][42][43][44][45] gas pressure sintered; SRBSN, sintered reaction-bonded silicon nitride 2,16,18,46,47 ; HP, hot pressing [48][49][50] ; SPS, spark plasma sintering 51,52 ; PLS, pressureless sintering 33 ; HPFS, hot-pressing flowing sintering.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…Numerous kinds of research have shown that increasing densification was crucial to improving both the thermal and mechanical properties of Si 3 N 4 ceramics [ 9 , 10 ]. Moreover, large grains can improve the heat transmission efficiency, and the low content of inter-granular secondary phase and lattice defects can reduce phonon scattering to improve thermal conductivity [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%